Cho A + 1 + 2 + 2^2 + 2^3 + .... + 2^2016 và B = 2^2017 . TÍnh A và B
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a2+b2+c2=ab+bc+ca
<=>2a2+2b2+2c2=2ab+2bc+2ca
<=>(a2-2ab+b2)+(b2-2bc+c2)+(c2-2ca+a2)=0
<=>(a-b)2+(b-c)2+(c-a)2=0
<=>a=b=c
mà a+b+c=3<=>a=b=c=1
=>P=0
\(a)\left|x\right|=2017\Rightarrow\hept{\begin{cases}x=-2017\\x=2017\end{cases}\Rightarrow}x=\pm2017\)
\(b)A=1+2^1+2^2+...+2^{2017}\)
\(2A=2+2^2+2^3+...+2^{2018}\)
\(2A-A=(2+2^2+2^3+...+2^{2018})-(1+2^2+2^3+...+2^{2017})\)
\(A=2^{2018}-1\)
...
Rồi còn khúc để bạn so sánh đó
Ta có: \(\dfrac{B}{A}=\dfrac{\dfrac{1}{2016}+\dfrac{2}{2015}+\dfrac{3}{2014}+...+\dfrac{2015}{2}+\dfrac{2016}{1}}{\dfrac{1}{2}+\dfrac{1}{3}+\dfrac{1}{4}+...+\dfrac{1}{2017}}\)
\(=\dfrac{1+\left(1+\dfrac{2015}{2}\right)+\left(1+\dfrac{2014}{3}\right)+...+\left(1+\dfrac{2}{2015}\right)+\left(1+\dfrac{1}{2016}\right)}{\dfrac{1}{2}+\dfrac{1}{3}+\dfrac{1}{4}+...+\dfrac{1}{2017}}\)
\(=\dfrac{\dfrac{2017}{2017}+\dfrac{2017}{2}+\dfrac{2017}{3}+...+\dfrac{2017}{2015}+\dfrac{2017}{2016}}{\dfrac{1}{2}+\dfrac{1}{3}+\dfrac{1}{4}+...+\dfrac{1}{2017}}\)
\(=\dfrac{2017\left(\dfrac{1}{2}+\dfrac{1}{3}+\dfrac{1}{4}+...+\dfrac{1}{2015}+\dfrac{1}{2016}+\dfrac{1}{2017}\right)}{\dfrac{1}{2}+\dfrac{1}{3}+\dfrac{1}{4}+...+\dfrac{1}{2015}+\dfrac{1}{2016}+\dfrac{1}{2017}}\)
\(=2017\)
a) Ta có:
S = 1 + 5 + 9 + 13 + ... + 2013 + 2017
S = (2017 + 1)[(2017 - 1) : 4 + 1] : 2
S = 2018.505 : 2
S = 1019090 ÷ 2
S = 509545
b) Ta có:
A = 1 + 3 + 32 + 33 + ... + 32016
3A = 3 + 32 + 33 + 34 + ... + 32017
3A - A = (3 + 32 + 33 + 34 + ... + 32017) - (1 + 3 + 32 + 33 + ... + 32016)
2A = 32017 - 1
A = \(\frac{3^{2017}-1}{2}\)
=> B - A = 32017 - \(\frac{3^{2017}-1}{2}\)
=> B - A = 32017 - \(\frac{3^{2017}}{2}-\frac{1}{2}\)
=> B - A = \(\frac{3^{2017}}{2}-0,5\)
\(A=\frac{1}{2018}+\frac{2}{2017}+...+\frac{2017}{2}+2018\)
\(=\left(\frac{1}{2018}+1\right)+\left(1+\frac{2}{2017}\right)+...+\left(\frac{2017}{2}+1\right)+1\)(2018 số hạng 1)
\(=\frac{2019}{2018}+\frac{2019}{2017}+...+\frac{2019}{2}+\frac{2019}{2019}=2019\left(\frac{1}{2}+\frac{1}{3}+...+\frac{1}{2019}\right)\)
Mà \(B=\frac{1}{2}+\frac{1}{3}+\frac{1}{4}+...+\frac{1}{2019}\)
=> Khi đó : \(\frac{A}{B}=\frac{2019\left(\frac{1}{2}+\frac{1}{3}+...+\frac{1}{2019}\right)}{\frac{1}{2}+\frac{1}{3}+...+\frac{1}{2019}}=2019\)
??????????????????????????????????????????????????????????????????????????????????????????????????????????????
a) 2^6 và 8^2;
8^2 = ( 2^4)^2 = 2^8
2^6 < 8^2
5^3 và 3^5 = 125 và 243 = 125 < 243
3^2 và 2^3 = 9 và 8 = 9 > 8
2^6 và 6^2
6^2 = (
\(2A=2+2^2+2^3+2^4+...+2^{2017}\)
\(A=2A-A=2^{2017}-1\)
=> A<B